Roles of Achieved Levels of Low-Density Lipoprotein Cholesterol and High-Sensitivity C-Reactive Protein on Cardiovascular Outcome in Statin Therapy - Myung Han Hyun; Yuchang Lee; Byoung Geol Choi; Jin Oh Na; Cheol Ung Choi; Jin Won Kim; Eung Ju Kim; Seung-Woon Rha; Chang Gyu Park; Eunmi Lee; Hong Seog Seo (Cardiovascular Therapeutics)
In statin therapy, the prognostic role of achieved low-density lipoprotein cholesterol (LDL-C) and high-sensitivity C-reactive protein (hsCRP) in cardiovascular outcomes has not been fully elucidated. A total of 4,803 percutaneous coronary intervention (PCI)-naïve patients who prescribed moderate intensity of statin therapy were followed up. Total and each component of major adverse cardiovascular events (MACE) according to LDL-C and hsCRP quartiles were compared. The incidence of 5-year total MACEs in the highest quartile group according to the followed-up hsCRP was higher than that in the lowest quartile (hazard ratio (HR) = 2.16, p<0.001). However, there was no difference between the highest and lowest quartiles of the achieved LDL-C (HR = 0.95, p=0.743). After adjustment of potential confounders, the incidence of total death, de novo PCI, atrial fibrillation, and heart failure in the highest quartile of followed-up hsCRP, was higher than that in the lowest quartile (all p<0.05). However, other components except for de novo PCI in the highest quartile by achieved LDL-C was not different to that in the lowest quartile. These results suggest that followed-up hsCRP can be more useful for predicting future cardiovascular outcome than achieved LDL-C in PCI-naïve patients with statin therapy.